2009
DOI: 10.1007/s00520-009-0798-9
|View full text |Cite
|
Sign up to set email alerts
|

Standardized phase angle from bioelectrical impedance analysis as prognostic factor for survival in patients with cancer

Abstract: The present study demonstrates that PA, used as SPA, is an independent prognostic indicator in this group of cancer patients receiving chemotherapy treatment even after adjustment for other prognostic variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
2
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 21 publications
2
89
2
6
Order By: Relevance
“…This reveals that the phase angle, which is a valid nutritional marker and independent indicator of survival for patients receiving chemotherapy, 16,[18][19][20]31 was extremely low in this cohort. Within this cohort, we also investigated the validity of these nutritional markers as risk factors for outcomes after alloHCT and found that the pre-transplant phase angle is an independent predictor for 2-year overall survival, relapse mortality and progression-free survival (Urbain, unpublished data).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This reveals that the phase angle, which is a valid nutritional marker and independent indicator of survival for patients receiving chemotherapy, 16,[18][19][20]31 was extremely low in this cohort. Within this cohort, we also investigated the validity of these nutritional markers as risk factors for outcomes after alloHCT and found that the pre-transplant phase angle is an independent predictor for 2-year overall survival, relapse mortality and progression-free survival (Urbain, unpublished data).…”
Section: Discussionmentioning
confidence: 69%
“…15,30 The phase angle, one of the raw data obtained from bioelectrical impedance analysis measurements and therefore independent from the equipment and internal algorithms used, has proved to be a good prognostic, nutritional and membrane cell function marker in various diseases. 18,21,31,32 Sex-, age-and BMI-specific reference values of the phase angle from a large healthy German population 33 34 The transformation of phase angle values into standardized values (Z-score) allows us to quantify individual deviations from sex-, age-and BMI-specific population averages and to compare subjects from a heterogeneous group. Furthermore, Norman et al 16 showed that this standardization clearly enhances the phase angle's predictive power.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…Earlier studies of bia in patients with cancer have mostly had a retrospective design [30][31][32][33] and have enrolled patients with mixed cancers or varying stages of disease 14,36,40,44,45 . The key issues in the prognosis of hnc patients are disease stage and tumour grade, but an effect of prior treatment was avoided because our study enrolled only treatment-naïve hospitalized patients with stage iii or iv disease.…”
Section: Discussionmentioning
confidence: 99%
“…Bioelectrical impedance analysis (BIA) is a tool that utilises the phase angle (PA) to evaluate the progress of liver cirrhosis in a practical way that meets the clinical requirements by reporting on body and cell structure, even in cases of body asymmetry. The PA enables the determination of cellular structure and function, thus indirectly improving the efficacy of nutritional interventions (1,13,17,31,32) . Cirrhotic patients may present with several nutritional deficiencies, including zinc deficiency; zinc participates in homeostasis and the formation of protein structures.…”
Section: Alteration Of Taste Buds In Experimental Cirrhosis Is Therementioning
confidence: 99%